2016
DOI: 10.18805/ijar.11162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of growth hormone releasing hormonegene in exotic and crossbred pigs

Abstract: Growth hormone releasing hormone (GHRH) plays a central role in growth and production through its influence on important metabolic activities in mammals which prompted its wide commercial use including use as a candidate marker. In present experiment, polymorphism at exon 2 and 3 of Growth Hormone Releasing Hormone gene (GHRH) was studied using PCR-RFLP in crossbred and exotic pigs, commonly found in north east India. Restriction enzyme digestion of 467 bp PCR amplicon with AluI revealed 1 genotype. Comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Primers were synthesized by Nanjing Kinco Biotech Co., Ltd (Nanjing, China) and their coordinates in the reference genome, annealing temperature and sequences were supplied in Table S2. The PCR (Kaushik et al 2017) amplification time was determined according to the target fragment size.…”
Section: Primer Design and Synthesismentioning
confidence: 99%
“…Primers were synthesized by Nanjing Kinco Biotech Co., Ltd (Nanjing, China) and their coordinates in the reference genome, annealing temperature and sequences were supplied in Table S2. The PCR (Kaushik et al 2017) amplification time was determined according to the target fragment size.…”
Section: Primer Design and Synthesismentioning
confidence: 99%
“…Pourouchottamane et al (2013) reported similar observations with the present findings in case of Ghungroo (8.758±0.542 kg and 46.83±3.597kg) pigs. Kaushik et al (2013) reported higher birth weight of GH × HS pigs in organised farm. There was significant (P<0.05) difference in body weight at 6 months and 9 months of age in Ghungroo (34.28±0.59 kg and 44.21±0.97 kg), Ghungroo × Hampshire (48.91±0.55 kg and 65.30±1.37 kg) and nondescript local (21.52±0.36 kg and 36.67±0.88 kg).…”
mentioning
confidence: 90%